2014
DOI: 10.1068/a45370
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Globalization on the Distribution of Taxes and Social Expenditures in Europe: Do Welfare State Regimes Matter?

Abstract: Europe. It tests the coexistence of efficiency and compensation effects of globalization on the expenditure as well as the revenue sides of government budgets. In Western Europe, globalization leads to an increase in social expenditures; however these expenditures are to an increasing extent financed by taxes on labor income. There is no effect of the ITR on capital income, whereas the ITR on consumption decreases. There are important differences between the welfare states. In the conservative regimes, social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 76 publications
(132 reference statements)
2
27
0
1
Order By: Relevance
“…Both approaches show that, in CEE NMS, globalisation was not correlated with ITRs on labour and negatively correlated with ITRs on consumption. Globalisation was somewhat positively correlated with ITRs on capital in CEE NMS (Onaran and Boesch, ). Onaran and Boesch () distinguish among the CEE NMS between ‘post‐communist European type’ and ‘Baltic type’ countries and concluded that there is no negative association between globalisation and ITRs on consumption in the Baltic type countries.…”
Section: Hypotheses and Empirical Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Both approaches show that, in CEE NMS, globalisation was not correlated with ITRs on labour and negatively correlated with ITRs on consumption. Globalisation was somewhat positively correlated with ITRs on capital in CEE NMS (Onaran and Boesch, ). Onaran and Boesch () distinguish among the CEE NMS between ‘post‐communist European type’ and ‘Baltic type’ countries and concluded that there is no negative association between globalisation and ITRs on consumption in the Baltic type countries.…”
Section: Hypotheses and Empirical Evidencementioning
confidence: 99%
“…Globalisation was somewhat positively correlated with ITRs on capital in CEE NMS (Onaran and Boesch, ). Onaran and Boesch () distinguish among the CEE NMS between ‘post‐communist European type’ and ‘Baltic type’ countries and concluded that there is no negative association between globalisation and ITRs on consumption in the Baltic type countries. Because the authors do not compute a marginal effect of globalisation for the Baltic type countries, we do, however, not know whether the marginal effect of globalisation in the Baltic countries is negative and statistically significant.…”
Section: Hypotheses and Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…For example, most recently Egger et al (2016), Tanninen et al (2017); earlier studies include Kwon and Pontusson (2010), Lupu andPontusson (2011), Meinhard andPotrafke (2012), Dreher (2005), Rodrik (1998), Onaran and Boesch (2014), Gemmel et al (2008). See also Potrafke (2009) for a study on the effect of globalisation on partisan politics.…”
Section: Globalisation and Technological Changementioning
confidence: 99%
“…31 See Potrafke (2015) for a recent survey. For example, most recently Egger et al (2016), Tanninen et al (2017); earlier studies include Kwon and Pontusson (2010), Lupu andPontusson (2011), Meinhard andPotrafke (2012), Dreher (2005), Rodrik (1998), Onaran and Boesch (2014), Gemmel et al (2008). See also Potrafke (2009) for a study on the effect of globalisation on partisan politics.…”
Section: Globalisation and Technological Changementioning
confidence: 99%